(untitled) - Bhujel, Ram C. (Oxford, UK, 2008)
This book is a nice guide to start doing statistic in marine biology. I strongly recommend it for under and graduate students in the field.
Thống kê ứng dụng và viết báo cáo khoa học
Keywords: Nuôi trồng thủy sản,Aquaculture